Ability of students to recognize the relationship between using mobile apps for learning during fieldwork and the development of graduate attributes. Issue 2 (2nd April 2016) - France, Derek; Powell, Victoria; Mauchline, Alice L.; Welsh, Katharine; Park, Julian; Whalley, W. Brian; Rewhorn, Sonja
Abstract: The increasing importance of employability in Higher Education curricula and the prevalence of using mobile devices for field-based learning prompted an investigation into student awareness of the relationship between the use of mobile apps for learning and the development of graduate attributes (GAs) (and the link to employability). The results from post-fieldwork focus groups from four field courses indicated that students could make clear links between the use of a variety of mobile apps and graduate attribute development. The study suggests a number of mobile apps can align simultaneously with more than one graduate attribute. Furthermore, prior experience and the context of use can influence students' perceptions of an app and its link with different GAs.